2020
DOI: 10.1029/2019gl085868
|View full text |Cite
|
Sign up to set email alerts
|

Poleward Shift of the Major Ocean Gyres Detected in a Warming Climate

Abstract: Recent evidence shows that wind‐driven ocean currents, like the western boundary currents, are strongly affected by global warming. However, due to insufficient observations both on temporal and spatial scales, the impact of climate change on large‐scale ocean gyres is still not clear. Here, based on satellite observations of sea surface height and sea surface temperature, we find a consistent poleward shift of the major ocean gyres. Due to strong natural variability, most of the observed ocean gyre shifts are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
133
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 148 publications
(162 citation statements)
references
References 58 publications
11
133
0
2
Order By: Relevance
“…During the past decades, a consistent poleward shift of the major subtropical ocean gyres driven by climate change has been reported, and a stronger surface ocean warming trend has occurred over the western boundary currents of the oceans (Wu et al, 2012;Yang et al, 2016Yang et al, , 2020. In the South Atlantic Ocean, a poleward displacement of the subtropical gyre at a rate of 0.11 • /decade has been observed (Yang et al, 2020), and the western boundary current -the Brazil Current (BC) -has been reported as one of the most extensive and intense surface warming hotspots in the global ocean (Hobday and Pecl, 2014).…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…During the past decades, a consistent poleward shift of the major subtropical ocean gyres driven by climate change has been reported, and a stronger surface ocean warming trend has occurred over the western boundary currents of the oceans (Wu et al, 2012;Yang et al, 2016Yang et al, , 2020. In the South Atlantic Ocean, a poleward displacement of the subtropical gyre at a rate of 0.11 • /decade has been observed (Yang et al, 2020), and the western boundary current -the Brazil Current (BC) -has been reported as one of the most extensive and intense surface warming hotspots in the global ocean (Hobday and Pecl, 2014).…”
Section: Introductionmentioning
confidence: 90%
“…During the past decades, a consistent poleward shift of the major subtropical ocean gyres driven by climate change has been reported, and a stronger surface ocean warming trend has occurred over the western boundary currents of the oceans (Wu et al, 2012;Yang et al, 2016Yang et al, , 2020. In the South Atlantic Ocean, a poleward displacement of the subtropical gyre at a rate of 0.11 • /decade has been observed (Yang et al, 2020), and the western boundary current -the Brazil Current (BC) -has been reported as one of the most extensive and intense surface warming hotspots in the global ocean (Hobday and Pecl, 2014). Although changes in the distribution and productivity of marine species have been recorded over faster ocean warming regions worldwide (Burrows et al, 2014;Sunday et al, 2015;Pecl et al, 2017), potential changes remain largely unexplored in the southwest South Atlantic Ocean (SWAO, see Franco et al, 2020).…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“… Ozeanzirkulation Darstellung der großen windgetriebenen Ozeanzirkulation (schwarze Pfeile) und ihrer Verlagerung (weiße Pfeile) unter globaler Erwärmung (nach ). …”
Section: Abbunclassified
“…Mit unserer Methode kann man auch abschätzen, wie groß der anthropogen verursachte Trend gegenüber natürlichen Fluktuationen ist, und wie schnell sich die Ozeanzirkulation verschiebt. Demnach bewegt sich die großräumige Zirkulation mit einer durchschnittlichen Geschwindigkeit von 800 Metern pro Jahr polwärts . Auch die Aufzeichnungen der Ozeansedimente vom Meeresboden, die vergangene Klimawechsel aufzeigen können, zeigen, dass während der letzten Eiszeit vor 21000 Jahren Teile der Ozeanzirkulation im Vergleich zu ihrer heutigen Position 800 km näher am Äquator gelegen haben.…”
Section: Abbunclassified